Model of complex searching over structured P2P overlay under dynamic environment - Khan, Saiful; Gani, Abdullah (International Association of Computer Science and Information Technology Press (IACSIT), 2012)
This paper aims to present a model to achieve complex searching (e.g. Wild card searching, blind searching, full text searching, metadata searching, etc.) over Structured P2P Overlay under dynamic environment. Lack of complex searching over Structured Overlay network and poor resilience due to peer dynamics makes it unsuitable for implementing the P2P systems and thus makes it very unpopular. In implementing the complex searching technique in structured overlay, the query must be processed by each node (peer) locally. This requires query to be efficiently broadcasted to all the nodes. However, broadcasting based algorithms tend to perform badly under highly dynamic environment and also create huge amount of maintenance traffic. This paper proposes a model which combines broadcasting based algorithm with efficient maintenance algorithm, which will reduce the maintenance traffic and increase the search efficiency.